Henri Dutilleux : his life and works - Potter, Caroline (Hants Ashgate, 2001)
This volume examines the music of French composer Henri Dutilleux (b. 1916), tracing the evolution of his musical style from the early works and investigating his compositional process and his use of particular referential devices in his later works. Also examined is Dutilleux's engagement with the work of other artists, from the writing of Baudela